Francisella tularensis ΔpyrF Mutants Show that Replication in Nonmacrophages Is Sufficient for Pathogenesis In Vivo - Horzempa, Joseph (American Society for Microbiology (ASM), 2010)
The pathogenesis of Francisella tularensis has been associated with this bacterium's ability to replicate within macrophages. F. tularensis can also invade and replicate in a variety of nonphagocytic host cells, including lung and kidney epithelial cells and hepatocytes. As uracil biosynthesis is a central metabolic pathway usually necessary for pathogens, we characterized ΔpyrF mutants of both F. tularensis LVS and Schu S4 to investigate the role of these mutants in intracellular growth. As expected, these mutant strains were deficient in de novo pyrimidine biosynthesis and were resistant to 5-fluoroorotic acid, which is converted to a toxic product by functional PyrF. The F. tularensis ΔpyrF mutants could not replicate in primary human macrophages. The inability to replicate in macrophages suggested that the F. tularensis ΔpyrF strains would be attenuated in animal infection models. Surprisingly, these mutants retained virulence during infection of chicken embryos and in the murine model of pneumonic tularemia. We hypothesized that the F. tularensis ΔpyrF strains may replicate in cells other than macrophages to account for their virulence. In support of this, F. tularensis ΔpyrF mutants replicated in HEK-293 cells and normal human fibroblasts in vitro. Moreover, immunofluorescence microscopy showed abundant staining of wild-type and mutant bacteria in nonmacrophage cells in the lungs of infected mice. These findings indicate that replication in nonmacrophages contributes to the pathogenesis of F. tularensis.